AI-Powered Multilingual Mental Health Chatbot with Personalized Voice and Text Support on Streamlit - Sharmila G.; Aiswarya Raj; Prithiga R.; Sasi Aditi G.K.; Shree Nithi C. (International Journal of Computer Science Languages, 2025)
Mental health concerns are increasingly recognized as one of the most pressing global challenges, with millions of people struggling to access timely, affordable, and personalized support. Barriers such as stigma, lack of professional availability, language differences, and geographical limitations often prevent individuals from seeking help when they need it most. To address this critical gap, this study introduces MindMate, an AI-powered multilingual chatbot specifically designed to provide both text-based and voice-enabled mental health assistance through an easy-to-use Streamlit interface. Built on the Rasa framework, the system incorporates advanced natural language understanding and dialogue management to engage in meaningful, empathetic interactions. MindMate is capable of processing multiple languages by integrating multilingual models, while also including speech recognition for seamless voice input. Furthermore, it employs a personalized recommendation engine that suggests relevant coping strategies, resources, and self-care practices tailored to each user’s needs. By prioritizing inclusivity, accessibility, and emotional sensitivity, MindMate offers a safe, judgment-free space for individuals to share their concerns. Experimental evaluations highlight its efficiency, accuracy, and cultural adaptability, underscoring its potential to transform digital mental health support services worldwide.
Keywords: Mental health chatbot; Rasa framework; Streamlit; multilingual support; natural language understanding; personalized responses; speech recognition